2D MXene incorporated nickel hydroxide composite for supercapacitor application - Lokhande, P. E.; Jagtap, Chaitali; Kadam, Vishal; Udayabhaskar, R.; Kumar, Deepak; Ali Al-Asbahi, Bandar; Anil Kumar, Yedluri (Journal of materials science. Materials in electronics, 2024)
In the current investigation, we report the successful synthesis of a novel Ni(OH) 2 /Ti 3 C 2 T x MXene nanocomposite via a microwave-assisted technique, specifically tailored for supercapacitor applications. The inherent semiconductor properties of nickel hydroxide often impede its electrochemical capabilities; however, the integration with a conductive host material can significantly ameliorate this limitation. To this end, Titanium Carbide (Ti 3 C 2 T x ) was incorporated during the Nickel Hydroxide (Ni(OH) 2 ) synthesis process, resulting in the in-situ formation of Ni(OH) 2 nanosheets homogeneously anchored onto the MXene sheets. The electrode derived from this nanocomposite showcased exceptional electrochemical attributes. Notably, it achieved a remarkable-specific capacitance peak of 675 Fg −1 at a current density of 2 Ag −1 , coupled with outstanding stability and cyclability metrics. Furthermore, the asymmetric supercapacitor engineered with the synthesized material attained an energy density of 9.25 Whkg −1 and a power density of 3.2 kWkg −1 . This device not only demonstrated superior rate capability but also sustained cyclic stability. The empirical evidence gathered from these experiments underscores the promising potential of metal hydroxide/MXene nanocomposites in advancing supercapacitor technology.